Tablero para la visualización de los datos generados de los incidentes reportados y gestionados en el Centro Regulador de Urgencias y Emergencias CRUE de la Secretaría Distrital de Salud de Bogotá (2021)
The Ministry of Health, as rector of health at the district level, has the Center Regulator of Emergencies and Emergencies in Health, which is part of the agencies that According to the emergency line 123 of the capital district, it is in charge of receiving and managing requests for urgencies and emergencies in health through the information system premier one. The information system is designed for resource management in patient care. incidents in real time and does not have a BI tool that allows the consultation of information and visualization of historical data that support decision-making from the managerial level. The objective of the project is based on the development of a control panel that allows the visualization of summarized information of the process of dispatches, attentions and transfers generated from incident management. To achieve the objective described above, the use of a database management system is implemented. data in this case SQL Server, the integration of data through SQL server Integration services and visualization through the Microsoft Power Bi tool.